Assisted reproductive technology in Japan: A summary report for 2022 by the Ethics Committee of the Japan Society of Obstetrics and Gynecology - Yukiko Katagiri; Seung Chik Jwa; Akira Kuwahara; Takeshi Iwasa; Masanori Ono; Keiichi Kato; Hiroshi Kishi; Yoshimitsu Kuwabara; Fuminori Taniguchi; Miyuki Harada; Akira Iwase; Norihiro Sugino (Reproductive Medicine and Biology)
Abstract Purpose This descriptive analysis evaluated the 2022 assisted reproductive technology (ART) data collected by the Japan Society of Obstetrics and Gynecology registry. Methods and Results In 2022 (cutoff date 30 November 2023), 634 of 635 registered ART facilities participated; 602 implemented ART treatment, with 543 630 registered cycles and 77 206 neonates (9.1% and 10.6% increases from the previous year). For fresh cycles, freeze‐all in vitro fertilization and intracytoplasmic sperm injection cycles increased, resulting in 2183 and 2822 neonates, respectively. In total, 275 296 cycles resulted in oocyte retrieval, with 158 247 (57.5%) freeze‐all cycles. Total single embryo transfer (ET) and singleton pregnancy rates were 82.4% and 97.2%, respectively. The singleton live birth rate was 97.4%. The number of frozen–thawed ET (FET) cycles was 264 412, with 98 348 pregnancies and 72 201 neonates. The single ET rate was 85.3%. The rate of singleton pregnancies was 96.9%; that of singleton live births was 96.9%. Per registered cycle, women had a mean age of 37.6 (standard deviation: 4.8) years; 210 322 cycles (38.7%) were conducted for women aged ≥40 years. Conclusions Significant growth in ART cycles and outcomes reflects the impact of recent expanded insurance coverage.